THE INFLUENCE OF ISLAMIC FINANCIAL LITERACY ON ISLAMIC FINANCIAL INCLUSION OF ECONOMIC EDUCATION STUDENTS OF STAMBUK 2023 AT MEDAN STATE UNIVERSITY - Dwi Atika Zahara; Fais Irawan; Khairunnisa Umi Al Mas; Sabrina Erisa Aulia Sihotang; Siti Mardiah (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2025)
Indonesia is a country that has the largest Muslim population in the world, the potential that Indonesia has is quite large in the development of the Islamic banking and finance sector. This research focuses on Economics Education students of Stambuk 2023 to analyze their level of Islamic financial literacy and its influence on Islamic financial inclusion. Hopefully, this research can provide deeper insights into the relationship between Islamic financial literacy and inclusion. This research uses quantitative methods with an associative approach, as well as primary data analyzed through computational tests with simple linear regression techniques. The research sample consisted of 30 students selected using probability sampling and purposive sampling methods. The research instrument was a questionnaire distributed indirectly to respondents, with a questionnaire containing open questions and five answer choices. Data analysis was carried out using inferential analysis techniques. Based on the results of the t test, the calculated t value is 3.142, which is greater than the t table of 1.70133 (3.142> 1.70133), as well as a significance value of 0.004 which is smaller than 0.05 (0.004 < 0.05). These results show that the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted, which indicates that there is a positive and significant relationship between financial literacy and financial inclusion. Thus, the higher a person's financial literacy, the more likely they are to access and utilize various products from formal financial services, including Islamic finance.